Effect of convection on the thermal structure of the troposphere and lower stratosphere including the tropical tropopause layer in the South Asian monsoon region. (April 2018) - Muhsin, M.; Sunilkumar, S.V.; Venkat Ratnam, M.; Parameswaran, K.; Krishna Murthy, B.V.; Emmanuel, Maria
Abstract: Influence of convection on the thermal structure of Troposphere and Lower Stratosphere (TLS) is investigated using radiosonde data, obtained from Trivandrum (8.5°N, 76.9°E), Gadanki (13.5°N, 79.2°E), Bhubaneswar (20.25°N, 85.83°E), Kolkata (22.65°N, 88.45°E) and Singapore (1.37°N, 103.98°E), collected during different convective categories classified based on the altitude of deep convective cloud tops (CT) in the period 2008–2014. During deep convective events, the temperature showed lower tropospheric cooling, an upper tropospheric warming and an anomalous cooling (warming) below (above) the cold point tropopause (CPT) with respect to the clear-sky value. While warming in the upper troposphere is strongest (∼2–4 K) around 10–12 km, anomalous cooling (warming) below (above) the CPT is maximum around 15.5 km (17.5 km) with values in the range of−2 to −4 K (3–6 K). These temperature perturbations are observed 5–6 days prior to the convective events. In response to deep convection, surface cooling up to ∼ −4 K is also observed. This study showed that the magnitude of cold and warm anomalies increases with strength of convection. During deep convection, the potential temperature (θ) shows a decrease (<5 K) in the tropical tropopause layer (TTL) from the TTL-base up to CPT compared to that on clear-sky days, confirming the vertical mixing of convective air from the lower atmosphere to the TTL-levels. Correlation analysis between different TTL parameters suggests that, as the cloud top altitude increases, along with the adiabatic process, diabatic process also plays a major role in the TTL. An interesting feature observed during deep convection is the ascent of TTL-base by ∼1.5 km and descent of CPT and TTL-top by 0.5 km, which effectively thins the TTL by ∼2 km. Highlights: Troposphere and lower stratosphere temperature perturbations in response to varying convective intensities are quantified. Temperature perturbations are observed 5 to 6 days prior to the convective events. Higher the convective intensity, thinner the TTL. Deep convection reaching altitudes >12 km shrink the TTL by 2 km. Relative role of diabatic process in modulating the TTL increases with the strength of convection.